European Social Policy and Europe's Party-Political Center of Gravity, 1957-2003 - Hendrik Zorn; Armin Schäfer; Philip Manow (Max Planck Institute for the Study of Societies, 2004)
Europe's 'political space', its dimensionality and its impact on European policies have received increased academic attention lately. Yet, one very basic element of this political space, the party composition of EU member states' governments, has never been studied in a systematic way in the rich literature on European integration. In this paper we explain why the EU literature would benefit from a closer analysis of Europe's party-political 'center of gravity'. We give a systematic overview of the party composition of member governments from 1957 to 2003. This includes analyses of how the support for integration, the left/right political conviction, and the ideological homogeneity or heterogeneity of the member states affected strictly intergovernmentalist EU institutions like the Council over the course of time. We draw on expert surveys, the data of the Comparative Manifesto Project, and data about government composition. Our case study about the fate of European social policy from the Treaty of Rome to the present day highlights the argument that analyses of European integration require an understanding of the party-political dimension of this process. – – In den letzten Jahren ist Europas 'politischer Raum', seine Dimensionalität sowie sein Einfluss auf einzelne Politiken zunehmend in den Mittelpunkt akademischen Interesses gerückt. Trotz einer Vielzahl bestehender Studien wurde jedoch ein zentrales Element dieses politischen Raums bisher nicht systematisch untersucht: die parteipolitische Zusammensetzung der Regierungen der Mitgliedstaaten. In diesem Papier zeigen wir, weshalb die Analyse des parteipolitischen 'Gravitationszentrums' der EU mehr Beachtung in der Literatur finden sollte, und liefern eine erste systematische Darstellung der Regierungszusammensetzung aller Mitgliedstaaten von 1957 bis 2003. Darüber hinaus wird untersucht, wie integrationsfreundlich, links oder rechts sowie ideologisch homogen bzw. heterogen die Mitgliedstaaten - und damit die intergouvernementalen EU-Gremien - im Zeitverlauf waren. Hierbei greifen wir auf Expertensurveys, Daten zur parteipolitischen Regierungszusammensetzung und Daten des Manifesto-Projektes zurück. Eine Fallstudie zur Entwicklung der EU-Sozialpolitik seit den Römer Verträgen ergänzt die quantitative Darstellung. Sie unterstreicht, dass die Analyse der Europäischen Integration ein angemessenes Verständnis der parteipolitischen Dimension des Einigungsprozesses voraussetzt.
Keywords: 300